(untitled) (Journal of the College of Basic Education, 2022)
The research aims to use strategy form the house ring in motor learning of the effectiveness of the javelin as well as to identify the impact of that strategy on the learners in motor learning of the effectiveness of the javelin and the development of hypotheses that fit and aim of the research, and the researcher to select a sample of students Faculty of Physical Education at the University of Qadisiyah, In action research researcher used التجريبيي and testing skills for effective javelin and the researcher extracted differences tests dimensional experimental group and the control group in a variable motor learning of the effectiveness of the javelin and the researcher to find ratios evolution in motor learning of the effectiveness of the javelin, and designed researcher curriculum for the experimental group and the researcher to performance evaluation skills for effective according to the views of specialists and experts in athletics, and data processing researcher used coefficient sprains to measure homogeneity sample and the value of T and the law of Growth After Almaaljajh statistical reviewed researcher results and deliberately Elly discussed and researcher concluded that the use of strategy form the house ring has affected a significant effect in Learn effective javelin in favor of the experimental group and through extraction Growth found that the rate of evolution in the experimental group than the proportion of development in the control group, the harbor, the researcher recommended using a strategy House ring because of their impact in motor learning of the effectiveness of the javelin